Enhancing Elementary School Students' Science Learning Outcomes Through the Use of Simple Instructional Media - Sonia Yulia Friska; Marthasya Eka Nuraini; Reva Alwa; Tiara Rahmadhani; Yopani Reza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Science education in elementary schools plays a strategic role in developing students' scientific thinking and science process skills. However, classroom practice often reveals suboptimal learning outcomes due to the predominance of teacher-centered instructional methods and the limited use of diverse learning media, making it difficult for students to visualize abstract scientific concepts. This study aims to examine the effectiveness of simple instructional media utilizing materials from the surrounding environment, such as recycled plastic bottles, mirrors, and plants, in improving students' science learning outcomes. The study employed a quantitative approach using a one-group pretest-posttest experimental design. The participants consisted of 30 fifth-grade elementary school students. Data were collected through learning achievement tests, classroom observations, and documentation. The findings indicate that the use of simple instructional media significantly improved students' science learning outcomes. The mean score increased substantially from 64.87 on the pretest to 84.20 on the posttest. In addition to cognitive improvement, students demonstrated higher levels of participation and enthusiasm during observation activities and group discussions. The simple instructional media effectively helped students visualize abstract concepts and relate them to real-life phenomena. These findings suggest that simple instructional media provide an effective, efficient, and contextually relevant alternative for enhancing the quality of science instruction in elementary schools while creating more meaningful and engaging learning experiences.